Salivary SARS-CoV-2 RNA for diagnosis of COVID-19 patients: A systematic review and meta-analysis of diagnostic accuracy - Douglas Carvalho Caixeta; Luiz Renato Paranhos; Cauane Blumenberg; Marcelo Augusto Garcia-Júnior; Marco Guevara-Vega; Elisa Borges Taveira; Marjorie Adriane Costa Nunes; Thúlio Marquez Cunha; Ana Carolina Gomes Jardim; Carlos Flores-Mir; Robinson Sabino-Silva (Japanese Dental Science Review, 2023)
Accurate, self-collected, and non-invasive diagnostics are critical to perform mass-screening diagnostic tests for COVID-19. This systematic review with meta-analysis evaluated the accuracy, sensitivity, and specificity of salivary diagnostics for COVID-19 based on SARS-CoV-2 RNA compared with the current reference tests using a nasopharyngeal swab (NPS) and/or oropharyngeal swab (OPS). An electronic search was performed in seven databases to find COVID-19 diagnostic studies simultaneously using saliva and NPS/OPS tests to detect SARS-CoV-2 by RT-PCR. The search resulted in 10,902 records, of which 44 studies were considered eligible. The total sample consisted of 14,043 participants from 21 countries. The accuracy, specificity, and sensitivity for saliva compared with the NPS/OPS was 94.3 % (95 %CI = 92.1;95.9), 96.4 % (95 %CI = 96.1;96.7), and 89.2 % (95 %CI = 85.5;92.0), respectively. Besides, the sensitivity of NPS/OPS was 90.3 % (95 %CI = 86.4;93.2) and saliva was 86.4 % (95 %CI = 82.1;89.8) compared to the combination of saliva and NPS/OPS as the gold standard. Based on low to moderate certainty level these findings suggest a similarity in SARS-CoV-2 RNA detection between NPS/OPS swabs and saliva, and the association of both testing approaches as a reference standard can increase by 3.6 % the SARS-CoV-2 detection compared with NPS/OPS alone. This study supports saliva as an attractive alternative for diagnostic platforms to provide a non-invasive detection of SARS-CoV-2.